(untitled) (American Journal of Islam and Society, 1986)
I. Introduction The educational process is a combination of three important elements: teacher, student, and communication. This study focused on the third element in examining second grade reading textbooks in four Arab countries: Jordan, Libya, Saudi Arabia, and Syria. Textbooks are not the only important element in the communication dimension nor do texts provide the only message students learn or the only influence in the educational process. Textbooks have the advantage, however, of being subject to content analysis and represent symbolic interaction as an effective means to translate the cultural heritage of any nation. Each country has its own books, and has its own methods to educate youngsters consistent with broad goals and national needs. Religious education in many Middle Eastern countries is a gradual and continuing process which begins early in the educational life of the individual. Such education is complete, comprehensive, and is intended even at the elementary level to develop understanding of religious and social behavior. Most of the content of books in Arab countries is prepared to reflect the separated worlds of males and females, displaying the supreme societal, religious, psychological, and physical power of men over women. Educational leaders and decision makers, at least in the Middle East, seem to be effective advocates of traditional values and are concerned with the positive impact of the educational process. The primary aims of the educational system in ...